When online learning becomes compulsory: Student nurses’ adoption of information communication technology in a private nursing education institution - Petra Bester (AOSIS, 2021)
Background: Integrating the use of information communication technology (ICT) in nursing curricula when preparing student nurses for the digital health future such as the sudden online learning as a result of the coronavirus disease 2019 (COVID-19) pandemic is vital. However, when student nurses in a South African private nursing education institution, struggled to complete obligatory online learning courses, nurse educators had to search for solutions.